1989
DOI: 10.1103/physrevlett.62.264
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Ablation in the Solid-DeuteriumZPinch

Abstract: We have performed one-dimensional magnetohydrodynamic computer calculations of the formation and evolution of the solid-deuterium-fiber Z pinch. With use of a tabulated atomic data base and "cold-start" initial conditions, our computations show that current is carried by hot plasma which has been ablated from the solid fiber. The computations suggest that the experimentally observed instability growth may coincide with the complete ablation of the central fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 5 publications
4
15
0
Order By: Relevance
“…[5][6][7][8] The results are also consistent with observation of Aivozov et al, 14 who reported a precursor plasma on axis before the wire array arrives; and the calculation Bobrova et al, 5 who predicted that the magnetic force on these inhomogeneous currents will pull them apart. The results are at odds with the conclusions drawn by Bloomberg et al 4 that the vaporization and ionization phase of the wires in an array is so short as to be of no consequence, and that the self-magnetic field of each wire will maintain their spatial integrity.…”
Section: Mg Coated Al Loadssupporting
confidence: 84%
See 3 more Smart Citations
“…[5][6][7][8] The results are also consistent with observation of Aivozov et al, 14 who reported a precursor plasma on axis before the wire array arrives; and the calculation Bobrova et al, 5 who predicted that the magnetic force on these inhomogeneous currents will pull them apart. The results are at odds with the conclusions drawn by Bloomberg et al 4 that the vaporization and ionization phase of the wires in an array is so short as to be of no consequence, and that the self-magnetic field of each wire will maintain their spatial integrity.…”
Section: Mg Coated Al Loadssupporting
confidence: 84%
“…These processes have been considered theoretically by numerous researchers. [5][6][7][8] HY-Tech's results also reveal parasitic current channel formation that has not been addressed in previous studies. These parasitic currents are formed by prepulse currents, flowing in the load, which outgas the wire at current levels below that required to vaporize the surface.…”
Section: B Current Channel Formationmentioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless, none of these improvements could explain the experimentally observed stability. With the use of a "cold-start" MHD simulation, Lindemuth et al calculated that the enhanced stability was due to the presence of the solid core of a fiber which lasted for a very long time [4]. The subsequent calculation showed that rather than enhancing the stability the core partially masked the evidence of instabilities [5].…”
Section: Introductionmentioning
confidence: 99%